CHANNEL FLOW AND CONTINENTAL COLLISION TECTONICS: AN OVERVIEW - Grujic D. (My University, 2006)
The principle of channel flow as defined in fluid dynamics has been used in continental geodynamics since the 1980s. The basic equations for one-dimensional flow introduced to geologists by Turcotte and Schubert were further developed by several research groups to meet the needs of specific studies. The most substantive differences among numerical models are results of different solutions for flow in crust, developed for different boundary conditions. The concept of channel flow has met with strong opposition and criticism from geophysicists and modellers. Although it is difficult to prove unambiguously that there is an active weak channel, it is still the most successful model to explain and predict the tectonics, metamorphism and exhumation of high-grade terranes in some orogens. Moreover, the concept of channel flow has stimulated novel approaches to the study of both the tectonics and metamorphism of large, hot orogens and the interaction between tectonic and surface processes. © The Geological Society of London 2006.